Deteksi Dini Penyakit Tidak Menular dan Edukasi Tuberkulosis pada Masyarakat Desa Mayangan Kabupaten Jombang - Evi Puspita Sari; Farach Khanifah; Lestari Ekowati; Eky Indyanty (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
Non-communicable diseases (NCDs) and tuberculosis (TB) remain major challenges in public health development in Indonesia. Low public awareness of the importance of regular health check-ups, combined with limited knowledge about tuberculosis prevention, may lead to delayed disease detection and increase the risk of complications and transmission. This community service activity aimed to increase public awareness through integrated health screening and tuberculosis education. The activity was conducted in Mayangan Village, Jogoroto District, Jombang Regency, involving 36 community members as participants. Health examinations included blood pressure, blood glucose, total cholesterol, and uric acid measurements using the Point-of-Care Testing (POCT) method, followed by tuberculosis education and health consultations. The examination results showed that most participants had results within the normal range. However, some participants had blood pressure, blood glucose, cholesterol, and uric acid levels above the reference values, indicating the need for further evaluation at healthcare facilities. The educational session received a positive response from the community and encouraged participants to better understand the importance of early detection of non-communicable diseases and tuberculosis prevention. The integration of health screening and health education represents an effective promotive and preventive approach to increasing public awareness of efforts to maintain and improve health.